Effect of Crop Canopy on Runoff, Soil Loss and Crop Yield in Red Soils - Basavaraja, P.K.; Mallikarjunappa Gowda, D.S.; Itnal, C.J. (Journal of Soil and Water Conservation, 2022)
To study the loss of runoff water and soil loss under different crop canopy, an experiment was initiated in shallow red soils, with runoffplots having a slope of 1.5 per cent, equipped witlxdevisors and runoff collecting tanks. The maximum runoff (20.75%) and soil loss (2042 kg/ha) was found under cultivated fallow and minimum runoff was found in Jowar sown across the slope (15.14%). Soil loss upto 1570 kg/ha can be checked by sowing Styloganthus hamata as compared to cultivated fallow, thereby additional 8.10 mm runoff can be stored as soil moisture. Similarly, available nutrient loss can also be checked by sowing the crops across the slope thereby increasing the crop yields.